Literature Review: Authentic Assessment in Vocational High Schools - Firmania, Nafisa; Sudira, Putu; Dahar Minghat, Asnul (International Journal of Engineering and Technology, 2018)
Assessment is an activity that must be done in each lesson. Educational assessment is the process of gathering and processing information to determine the achievement of student learning outcomes. A good assessment must be carried out both in the learning process and in the final learning outcomes. The teaching and learning process in Vocational High Schools includes an explanation of science or study subjects and practice. With the complexity of learning in the Vocational High School, the assessment that is applied must be appropriate and can include the assessment of students as a whole. The assessment applied at the Vocational High School at this time is authentic assessment, where the assessment assesses three aspects of each student. The three aspects namely knowledge assessment, skills assessment and attitude assessment. Authentic assessment measures the overall student learning outcomes because this assessment assesses the progress of student learning not just the end result of student learning. Vocational high school students are prepared to work, therefore not only knowledge and skills must be invested because attitude is more important than both aspects. In other words, vocational high school students must be able to balance their knowledge and skills and be accompanied by a good attitude in each process.Â Â